KEBIJAKAN PEMBINAAN ATLET PENYANDANG DISABILITAS OLEH DINAS KEPEMUDAAN DAN OLAHRAGA PROVINSI RIAU TAHUN 2017 - Retno Pangestika; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Sports for people with disabilities are part of the sports field that must be nurtured and developed by the Youth and Sports Service of the Riau Provincial Government. Sports for people with disabilities are used as a medium to develop their potential and talents, considering that every human being apart from having shortcomings also has his own strengths, abilities and uniqueness. Of course, in this case, it must get special attention from the government.          The purpose of this study is to determine the policies for athletes with disabilities by the Riau Province Youth and Sports Agency in 2017 and the factors that hinder the policy of developing athletes with disabilities by the Riau Province Youth and Sports Service in 2017. The theory used is the theory of policy implementation. The location of the research was carried out at the Youth and Sports Office of Riau Province. This research uses a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques.          The result of this research is that there is still a lack of communication that occurs between the Youth and Sports Service of Riau Province and the Regional Development Planning Agency for Research and Development of Riau Province which results in a reduced budget for athletes with disabilities. This has an impact on the lack of human resources in the form of companions and physical resources in the form of facilities and infrastructure. Then there is a lack of time for training and continuous coaching should be carried out for athletes with disabilities before and after the event, as well as providing unequal bonuses between athletes with disabilities and athletes with non-disabilities. The impact was felt in the form of a decrease in total medals won by athletes with disabilities in Riau Province in 2017 in facing the 2017 Peparpenas event. Keywords: Athlete Development Communication, Athlete Development Human Resources, Disposition, Bureaucratic Structure